RESULTS OF THE SHORT COMPARATIVE ANALYSIS OF MATHEMATICAL MODELS OF INFLUENCE OF THE IONOSPHERE OF THE EARTH ON ULTRA BROADBAND SIGNALS X-RANGE - M. M. Kasperovich; V. A. Kondratyonok (Системный анализ и прикладная информатика, 2015)
For range portrait formation at usage ultrabroadband linearly frequency-modulated signal in radar it is necessary to consider all distortions of an electromagnetic wave on a radio route. At observation over circumterraneousobjects the signal transits through an ionosphere. The electromagnetic wave in it will be exposed to non-linearity distortions, which transform of signal time structure. It leads to distance error origin. For its compensating it is necessary to use the mathematical model of signal distortions in an ionosphere.